Immunohistochemical Staining for Uroguanylin, a Satiety Hormone, is Decreased in Intestinal Tissue Specimens From Female Adolescents With Obesity. (May 2018) - Di Guglielmo, Matthew D; Perdue, Lacey; Adeyemi, Adebowale; van Golen, Kenneth L; Corao, Diana U
Gastrointestinal tract–secreted satiety hormones play a significant role in one of the largest health-care challenges for children and adults, obesity. Recent studies in mice identified a novel role for uroguanylin, the endogenous intestinal hormone that binds guanylyl cyclase C (GUCY2C), in regulating satiety via a gut-brain signaling pathway. Mice bred without GUCY2C receptors over-ate and developed obesity. We hypothesized that intestinal uroguanylin expression in pediatric patients with obesity would be lower than patients without obesity, and we attempted to examine the difference with immunohistochemistry. Retrospective chart review of gastrointestinal endoscopic procedures at an academic children's hospital identified patients with normal pathology findings on biopsy. Children aged 8–17 were included in the review; we analyzed biopsy samples from 20 matched pairs that differed only by body mass index (BMI)-for-age (average: 25%–75% vs. high: >95%). Biopsies of the duodenum, terminal ileum, ascending colon, and descending colon were subjected to immunohistochemistry for GUCY2C, uroguanylin, and the endogenous colonic hormone, guanylin. Intensity staining of all specimens was scored by a blinded pathologist. The overall staining intensity for females with high BMI-for-age was less for uroguanylin and guanylin as compared to average BMI-for-age females while GUCY2C staining was equal. Males did not exhibit different staining intensities for uroguanylin or guanylin. More matched female pairs had greater uroguanylin and guanylin staining in the average BMI-for-age cohort. The intestinal expression of uroguanylin, a key satiety hormone, appears to be diminished in female pediatric patients in the setting of obesity.